OPTIMASI PERTUMBUHAN AKAR PADI MELALUI AMELIORASI HARDPAN DENGAN APLIKASI PUPUK KANDANG SAPI - Isnaniar Rahmatul Azizah; Lolita Endang Susilowati; Dori Kusuma Jaya; Zaenal Arifin; Intan Lusiana Dewi (AGRICA, 2026)
Compacted soil (hardpan) conditions in rice fields restrict root growth, reduce nutrient uptake efficiency, and negatively affect crop productivity. This study aimed to examine the effect of manure application on rice root morphology and the improvement of soil physical properties in compacted rice fields. The research was conducted in Banyu Urip Village, Gerung District, West Lombok Regency, using a Randomized Block Design (RBD) with four manure doses (0, 2.5, 5, and 7.5 tons/ha) and four replications. Observed parameters included bulk density, particle density, porosity, permeability, root volume, and root dry weight. The initial soil condition showed a bulk density of 1.28 g/cm³, particle density of 2.10 g/cm³, porosity of 39%, and permeability of 0.8 cm/h, indicating compacted soil unfavorable for root development. The results showed that manure application significantly improved root growth and soil physical properties. Treatments of 5-7.5 tons/ha produced longer, more branched roots, reduced bulk and particle densities, and increased porosity and permeability, especially in the topsoil (0-6 cm). The 5 tons/ha dose was the most effective treatment for improving soil structure and aggregation without decreasing porosity due to excessive fine organic residues.